2021
DOI: 10.1016/j.jneuroim.2021.577746
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response in multiple sclerosis patients following PfizerBNT162b2 COVID19 vaccination: Up to 6 months cross-sectional study

Abstract: Appropriate immune response following COVID-19 vaccination is important in the context of disease-modifying treatments (DMTs). In a prospective cross-sectional study, we determined SARS-COV-2 IgG response up to 6 months following PfizerBNT162b2 vaccination in 414 multiple sclerosis (MS) patients and 89 healthy subjects. Protective response was demonstrated in untreated MS patients ( N = 76, 100%), treated with Cladribine ( N = 48, 100%), Dimethyl fumarate ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
95
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(110 citation statements)
references
References 16 publications
12
95
1
2
Order By: Relevance
“…The results of this study confirm and expand previous studies [1][2][3] by showing that pwMS on NTZ develop and maintain a 6-month humoral response after the first dose of a full COVID-19 vaccination cycle comparable to their healthy peers; moreover, we found that, in pwMS on NTZ, higher physical disability is associated with a lower humoral response over time. These findings are relevant for clinicians called to counsel about COVID-19 mRNA vaccine timing and booster doses in pwMS treated with NTZ.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study confirm and expand previous studies [1][2][3] by showing that pwMS on NTZ develop and maintain a 6-month humoral response after the first dose of a full COVID-19 vaccination cycle comparable to their healthy peers; moreover, we found that, in pwMS on NTZ, higher physical disability is associated with a lower humoral response over time. These findings are relevant for clinicians called to counsel about COVID-19 mRNA vaccine timing and booster doses in pwMS treated with NTZ.…”
Section: Discussionsupporting
confidence: 90%
“…In the first short-term study on pwMS on NTZ [1], in which levels of IgG antibodies to SARS-CoV-2 spike protein (anti-TSP IgG) were evaluated in 31 pwMS 7 days after the second dose of the BNT162b2 mRNA vaccine, the authors reported an efficient humoral response, with values comparable to those of age-and sex-matched healthy controls (HCs). In another cross-sectional study evaluating the humoral response ~ 3 months after the second BNT162b2 mRNA vaccine dose in 32 pwMS treated with NTZ, a positive humoral response was measured in all pwMS, with no significant differences on levels of anti-TSP IgG between the NTZ and HC groups [2]. A third study on a larger population of 100 pwMS on NTZ confirmed that 4 weeks after the second dose of a mRNA vaccine (BNT162b2 or mRNA-1273), all participants mounted a full humoral response [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, 82 studies were included for meta-analysis ( table 1 , supplementary table 2). 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 …”
Section: Resultsmentioning
confidence: 99%
“…There are cumulative data reporting that MS patients treated with fingolimod failed to develop humoral as well as cellular immune responses due to low lymphocyte counts and thus are not protected from COVID-19 infection [ 5 – 7 ]. A significant decrease in the antibody level was associated with the presence and degree of lymphopenia [ 8 , 9 ]. Inability to achieve immune protection can have deleterious effects for patients as they are at a greater risk of COVID-19 infection, need to preserve social distance and avoid social interactions that can lead to increased psychological stress [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%